Effect of Branch Pruning and NPK Fertilizer Dosage on Plant Growth and Yield of Baby Cucumber (Cucumis sativus L.) - Ramadhanti Choirunnisa; Agus Sulistyono; Saefurrohman Saefurrohman (The University of Lampung, 2025)
Cucumber (Cucumis sativus L.) is rich in nutrients and vitamins, an is popular for fresh salads and various processed foods. The objective of this work is to study the effects of branch pruning and NPK fertilizer dose on the growth and yield of baby cucumber in order to solve the decrease in cucumber production. The research was executed in Dander Village, Bojonegoro Regency, East Java. The experiment was performed according to a Randomized Block Design with two factors. The first factor is branch pruning, and the second factor is the dose of NPK fertilizer. Branch pruning was carried out in four ways: no pruning, pruning branches at nodes 1–3, nodes 1–4, and nodes 1–5. The NPK fertilizer dose was also applied at four levels: 800, 900, 1,000, and 1,100 kg/ha. The observed parameters included plant length, number of leaves, time to female flower appearance, fruit length, number of fruits per plant, total fruit weight per plant, and fruit weight per hectare. The data were analyzed using analysis of variance (ANOVA) and tested with HSD at 5%. The results showed that the combination of no pruning and the application of 1,100 kg/ha NPK fertilizer produced the best results in terms of fruit weight per hectare. Keywords: Baby cucumber, Branch pruning, Harvest, Macro-nutrients, Photosynthate translocation.